Quorum of intention in moral value - Hassan Farzi; Mojtaba Mesbah (اخلاق وحیانی)
Intention, as a conscious motivation that is preferred over other motivations when realizing a voluntary act, has a very important position in determining its moral value. The basic question is, from the perspective of Islam, what is the Nisab of intention in moral value? The aim of this article is to reach an answer to this question. For this purpose, using the philosophical method in addition to referring to verses and narrations, after introducing sincerity as a criterion for measuring the levels of intention, the Islamic moral school was examined. The results of the research indicate that by considering direction and power as two influential components in the level of intention, the Nisab of intention is drawn in proportion to the Nisab of faith. That is, from the perspective of Islam, an intention has a Nisab of moral value that stems from faith in God Almighty and, in the next stage, faith in prophecy and resurrection. In this case, the degree of its nearness, or in other words, the degree of sincerity in it, has reached the level necessary to ensure the individual's minimal happiness.